2011
DOI: 10.3109/09637486.2011.639748
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive healthy components of bulgur

Abstract: Bulgur has been one of the most important traditional Durum wheat products in Turkey and Middle Eastern countries for ages. The objective of this study was to reveal the composition of some healthy components of industrial bulgur samples produced in Turkey. Total starch, resistant starch, dietary fibre and total phenolic contents and their high-performance liquid chromatography (HPLC) profile and antioxidant capacity of bulgur samples using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…B). These results are in agreement with previous data reporting a higher antioxidant activity of buckwheat flour and bulgur pilaf than other cereal products. In all foods, TAC was higher in AE than in EE.…”
Section: Resultssupporting
confidence: 93%
“…B). These results are in agreement with previous data reporting a higher antioxidant activity of buckwheat flour and bulgur pilaf than other cereal products. In all foods, TAC was higher in AE than in EE.…”
Section: Resultssupporting
confidence: 93%
“…TPC of emmer wheat and bulgur samples is given in Figure 2. Tacer Caba et al (2012) investigated five different industrially produced durum bulgur samples' bioactive properties. In addition, wheat variety, location, soil structure, and climate may be the other factors.…”
Section: Total Polyphenol Contentmentioning
confidence: 99%
“…In addition, wheat variety, location, soil structure, and climate may be the other factors. It is thought that the existence of genetics and variety differences, cultivation conditions, production methods, and bran separation stage is very effective on TPC as in other bioactive parameters (Brandolini et al, 2013;Tacer Caba et al, 2012;Yilmaz & Koca, 2017). TPC decreased minimum in MC + HD sample to 989.08 ± 9.71 µg GAE/g DM (27.5% loss), followed by AC + HD and AC + MD samples, and the highest loss was determined in TC + MD 569 ± 9.69 µg GAE/g DM (58.3% loss), TC + HD, and MC + MD samples (p < .05).…”
Section: Total Polyphenol Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that consumption of adequate amounts of RS may improve glucose and lipid metabolism in rats, and positive mineral utilization was also reported (Lopez et al, 2001). It has been reported that RS had a significant reduction effect on fatness; as a result, RS titled as a bioactive component (Tacer Caba et al, 2012). Bioactive compounds are substances which stimulate the probiotic growth.…”
Section: Resistant Starchmentioning
confidence: 99%